Sistem Informasi Pengelolaan Data Penduduk di Desa Endalo Kecamatan Lintang kanan - Mirnawati, Mirnawati; Indra kanedi; Ricky Zulfiandry (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Basically, information technology was developed to make it easier for society in general to obtain information that is suitable for consumption. For government administration activities to process data, a computer program is required. The research method that the author uses in creating a multimedia-based promotional media information system is the waterfall method, namely a sequential software development process where this method has several sequential stages: requirements (needs analysis), system design (system design), coding and testing , program implementation and maintenance. The development of a Population Information System in Endalo Village, Lintang Kan District is an ongoing population data processing information system design. Efforts have been made to deal with various problems that have arisen using a system that has been designed, with an orientation towards population services. Therefore it can be concluded that: The data collection system is still written in books, as a result it will take a lot of time, and the population data recapitulation process will take a long time. The slow pace of producing reports for residents who were born and died as well as those who came and moved is still considered less than optimal because everything has to be searched first and then typed into Microsoft Word. With data storage in the form of a database, it is possible that there will be no data duplication. With this population information system, it is hoped that it can become a population service system that can improve services to the community.